Social policy in the post-crisis context of small island developing states: A synthesis - Leisa Perch; Rathin Roy (International Policy Centre for Inclusive Growth (IPC-IG), 2010)
[Introduction] This paper provides a synthesis of the multifaceted impact of the global economic crisis on Small Island Developing States (SIDS), focusing on the Pacific and Caribbean regions. It shows that the social investment agenda, which has underpinned so much of the development progress of SIDS, has been particularly challenged by the global economic crisis and will require innovations and policy changes by SIDS in order to sustain and advance beyond current achievements. Global action will be required to enhance the available fiscal space for these actions. Additionally, in the SIDS, particular attention needs to be paid to the design and implementation of social policies that reduce vulnerability, improve resilience to exogenous shocks, and thus lower the human and productivity costs of exposure to repeated shocks. These include high unemployment and underemployment, rising crime and persistent inequalities across income groups and between rural and urban communities. The transitive effects of such exogenous shocks on the incomes, food security and access to basic public goods of poor and vulnerable households demonstrate the need for a new policy approach, one that is better placed than current approaches to increase SIDS' resilience to future shocks. The synthesis, based largely on experiences of and lessons learned from five countries in the Pacific and five in the Caribbean, seeks to advocate a `paradigm shift' in global and national-level approaches to the development challenges facing SIDS.
Keywords: 330